Adherence to Mediterranean Diet and its main determinants in a sample of Italian adults: results from the ARIANNA cross-sectional survey - Cardamone, Erica; Iacoponi, Francesca; Di Benedetto, Rita; Lorenzoni, Giulia; Di Nucci, Annalisa; Zobec, Federica; Gregori, Dario; Silano, Marco (Frontiers in Nutrition, 2024)
Introduction: Over the last years, many Mediterranean countries, including Italy, have witnessed a shift away from the Mediterranean Diet, thus contributing to the high rates of overweight and obesity. The survey “Adherence to Mediterranean Diet in Italy (ARIANNA)” aimed to evaluate the Adherence to Mediterranean Diet (AMD) and its main determinants in the Italian population. Materials and Methods: This study started on March 2023 and was addressed to adults aged ≥17 years, born and resident in Italy, proficient in Italian. Data are collected electronically through a voluntary, anonymous and self-administered questionnaire on the project website. Univariate and then multivariate logistic regressions were performed to evaluate associations between AMD and demographic characteristics, socio-economic status, health status and lifestyle. Results: On a total of 3,732 completed questionnaires, the 87.70% of the respondents was female and the 71.28% was 17-40 years old. The 83.82% of the respondents had medium AMD, 11.33% low and only 4.85% high. The multivariate analysis revealed that being male (p<0.001), aged >40 years (p<0.05), workers (p≤0.001) and unemployed (p<0.05) the probability of having a lower AMD. Vegans and vegetarian's diets positively contributed to a higher AMD (p<0.001). Discussion: These results highlighted a medium AMD in the Italian adult participants and suggested the necessity to implement tailored public health intervention strategies to improve food habits.